SAYYID QUTHB DAN AL-TASHWIR AL-FANNI FI AL-QUR’AN - Ahmad Nur Fathoni; Dewi Murni (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2022)
This study aims to examine the literary method used in the Kitab al-Tashwīr al-Fanni fī al-Qur’ān (artistic depictions in the Qur’an) written by Sayyid Qutb. This book examines the beauty of the expressions of the Qur’an and analyzes the verses revealed in it. In addition, this book also explores the secrets of the beauty of the Qur’an, and is not just an anthology. The results of this study arrive at the result that the literary method used by Sayyid Qutb is a depiction method, namely the tashwir fanni method (artistic drawing). Artistic drawing is the basic rule in the stylistics of the Qur’an. And the phenomena that stand out in this description are takhyil (feeling imagination) and tajsim (similes). And this phenomenon must be expressed in a certain pattern. Because takhyil and tajsim are useless without stylistic patterns that are fully expressed.